Does matter have non-dispositional intrinsic qualities? Sydney Shoеmaker against quidditism (Actual Problems of Mind, 2023)
The article discusses the problem of the existence of the fundamental non-dispositional intrinsic qualities of matter (quiddities) and arguments for two opposite views, quidditism and dispositionalism (causal structuralism). In support of quidditism, arguments by Howard Robinson, John Foster and Philip Goff are deployed. These arguments highlight the incoherence or unintelligibility of the doctrine that the whole reality is just a network of causal relations without any qualitative filler in the nodes of the network. Sydney Shoemaker’s influential argument for dispositionalism, in the article “Causality and Properties”, is analysed and responded. The case is made that Shoemaker’s objections against the existence of fundamental properties whose identity “consists of something logically independent of their causal potentialities” can be neutralised on the assumption that our world is operated by ontologically fundamental laws of nature in virtue of which quiddities have constant causal potentialities. Quidditism with this assumption makes it possible to know all the same properties of matter as dispositionalism, viz., dispositional properties and spatiotemporal relations. So, pace Shoemaker, it has no “disastrous epistemological consequences”. Although such quidditism expands (as compared with dispositionalism) ontology by attributing matter not only with knowable dispositional properties (causal structures) but also with quiddities, which are in a sense unknowable, this ontological exuberance is justified by the need to avoid the vicious regress of powers entailed by dispositionalism.
Keywords: matter; intrinsic quality; quiddity; disposition; power; causality